ANALISA KINERJA ELECTRICAL SUBMERSIBLE PUMP (ESP) UNTUK OPTIMASI PRODUKSI SUMUR RPD PADA LAPANGAN RPT ZONA 11 JAWA TIMUR - Raypaldri Tuasamu; Henk Subekti; Azmain Noor Hatuwe (Journal Mechanical Engineering, 2025)
In the oil industry, Indonesian oil wells that initially could flow fluids naturally (natural flow) experience declining reservoir pressure over time, necessitating artificial lift methods. The RPD well in the RPT Field Zone 11 East Java uses an Electrical Submersible Pump (ESP) as an artificial lift method. This research aims to analyze ESP performance, optimize production, and assess the economic feasibility of its use. Analysis was conducted using the Inflow Performance Relationship (IPR) method with Vogel's equation to understand well production capability. The analysis results show that the maximum production rate (Qmax) of the RPD well is 1108 bpd, with a pump volumetric efficiency of 63%. Field testing produced 698 bpd at 94% water cut. For optimization, a comparison was made between ESP pump type DN1300 with 165 stages and ESP pump type TA1500 with 175 stages, resulting in an increase in volumetric efficiency from 63% to 68% and production increase from 698 bpd to 785 bpd. Economic analysis indicates that the reactivation of the RPD well using ESP is financially viable, with a Net Present Value (NPV) of $771,744, Internal Rate of Return (IRR) of 78.98%, and Benefit-Cost (B/C) ratio of 26.64 before optimization. After optimization with the TA1500 pump type, there was an economic improvement with NPV $812,450, IRR 84.15%, B/C ratio 30.21, and Pay Out Time (POT) reduced from 1.24 years to 1.08 years. Sensitivity analysis proves that this project remains economically viable under various scenarios of oil price changes, operational costs, and discount rates Keywords: Natural flow, Artificial lift, Electricial Submersible pump, Efficiency, Production optimization, Economic analysis.